The Impact of Networks on Finnish Education Export : Case Finland University - Nieminen, Jussi (fi=Turun yliopisto|en=University of Turku|, 2017)
Interest towards education export has seen a major rise in Finland during the past decade. This has been a strategic choice from the Ministry of Education and Culture, which took education export as a major part in the strategy of the internationalization of Finnish higher education institutions in 2009. As result, Finnish higher education institutions have established education export companies of their own to promote their services. This research examines the impact of networks to the internationalization of these companies. The research question is approached through nine different themes. Qualitative case study was chosen as the research method for this study. Finland University was selected as the case company due to the structure of the ownership of the company. The empirical data of the study was collected through a semi-structured interview with the CEO of Finland University and the interview themes were adopted from Zain & Ng’s conceptual framework for company internationalization. The findings of this research provide support to six of the nine factors that were suggested to be impacted by networks in Zain & Ng’s model. In case of Finland University, no support could be found for networks impacting: Trigger and motivation for internationalization intention; Cost and risk minimization; and Constraints for future on the international market. Even though support for all the nine factors was not found, it is clear that networks have a major impact on the internationalisation of Finnish education export companies owned by higher education institutions. Based on the findings of this study, four managerial implications were drawn: (1) the companies should invest in network creation; (2) the companies should pay attention to the maintenance and management of their networks; (3) diverse networks and connections create opportunities; and (4) opportunities lie in unexpected places. For further research, the suggestion is to study the internationalization of a wider range of education export companies owned by higher education institutions (both foreign and domestic) as well as to conduct researches about the internationalization of Finnish education export companies in general, regardless of whether they are owned by the private or public sector and compare their internationalization.